MODEL EVALUASI TERINTEGRASI DALAM PEMBELAJARAN MICROTEACHING MAHASISWA PENDIDIKAN BAHASA ARAB (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to analyze the effectiveness of an integrated evaluation model in microteaching for Arabic Language Education students. The evaluation model combines peer assessment, video-based reflection, and lecturer feedback in a teach–review–reflect–reteach cycle. The study used a descriptive qualitative method with 32 sixth-semester students at Makassar State University as participants. Data were collected through observation, video recordings, written reflections, and interviews, then analyzed thematically. The results showed a significant improvement in nine basic teaching skills, with the average score rising from 73 to 86. The most notable improvements were seen in the skills of opening lessons, managing classrooms, and varying teaching strategies. It can be concluded that the integrated evaluation model is effective in improving the pedagogical competence of Arabic language students and is recommended to be widely adopted in the practical learning of prospective educators. The use of video technology and peer assessment is key to the success of a collaborative and sustainable learning process.